Spherical polyelectrolyte brushes as carrier particles for proteins: An investigation of the structure of adsorbed and desorbed bovine serum albumin. Issue 2 (2004) - Jackler Jackler, G. G.; Wittemann Wittemann, A. A.; Ballauff Ballauff, M. M.; Czeslik Czeslik, C. C.
Abstract : The change in the secondary and tertiary structure of bovine serum albumin (BSA) induced by the interaction with spherical polyelectrolyte brushes (SPB) has been investigated using fluorescence and circular dichroism (CD) spectroscopy. The SPB consist of poly(acrylic acid) chains grafted to a poly(styrene) core. The colloidal SPB represent a new substrate for protein immobilization because their protein binding capacity can be controlled by the ionic strength of the solution: SPB bind large amounts of BSA at low ionic strength (pH=6.1), but they are largely protein resistant at moderate salt concentrations of 500 mM. The conformation of BSA which was labeled with the environmentally sensitive dansyl fluorophore was studied before adsorption to the SPB, in the adsorbed state, and after desorption from the SPB. In the adsorbed state the obtained fluorescence spectrum is red-shifted which indicates a hydration of the dansyl fluorophores due to a distortion of the tertiary structure of BSA. Fluorescence and CD spectroscopic analysis of BSA that was desorbed from the SPB shows that the adsorption-induced conformational changes are largely reversible. Convex constraint analysis of the observed CD spectra of BSA yield α-helix fractions of 68% and 57% before adsorption to and after desorption from the SPB, respectively. In a general view, the results of this study demonstrate that spherical polyelectrolyte brushes are suitable for a controlled immobilization and release of proteins without major conformational changes.